COMPUTING SYSTEM FOR SOLVING PROBLEMS OF SECURITY AND STABILITY OF RAILWAY ROLLING STOCK - Blokhin, E. P.; Zheleznov, K. I.; Ursuliak, L. V. (Science and Transport Progress, 2007)
The description of the developed computer system possibilities and its use to solve problems of motion safety and stability is given.